Discontinuation of antiplatelet therapy after stent-assisted coil embolisation of cerebral aneurysm: a nationwide cohort study - Joonsang Yoo; Jinkwon Kim; Jimin Jeon; Minyoul Baik (Stroke and Vascular Neurology)
Introduction Stent-assisted coil embolisation (SACE) for the treatment of unruptured cerebral aneurysms has been increasingly used. Long-term advantages of antiplatelet therapy (APT) post-SACE treatment are still not well understood. We investigated the long-term effects of APT on clinical prognosis after SACE.Patients and methods We conducted a retrospective study using nationwide health insurance claims data from South Korea, including patients with cerebral aneurysm treated with SACE from January 2009 to December 2020. The study outcomes consisted of the occurrence of cerebral infarction and major haemorrhage. To evaluate the impact of APT, we employed a multivariable time-dependent Cox proportional hazards regression model for each of the three distinct periods: 1–12 months, 12–24 months and >24 months after SACE.Results This study included 17 692 unruptured cerebral aneurysm patients treated with SACE. During the mean follow-up of 4.2 years, there were 379 (2.1%) patients with cerebral infarction and 190 (1.1%) patients with major haemorrhage. The percentage of patients receiving APT was 79.5% at 1 year, which gradually decreased to 58.3% at 2 years after SACE. APT was beneficial in preventing cerebral infarction within 12 months after SACE (adjusted HR (aHR) 0.56; 95% CI, 0.35 to 0.89; p=0.014). After 12 months, this association was not evident. APT increased the risk of haemorrhage after 24 months (aHR 1.76; 95% CI 1.11 to 2.87; p=0.016).Discussion and conclusion Our findings suggest that in patients with unruptured cerebral aneurysm treated with SACE, the reasonable duration of APT for preventing cerebral infarction might be 1 year after SACE.